# 6(x-2)+3(4-2x)=2x+1

## Simple and best practice solution for 6(x-2)+3(4-2x)=2x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 6(x-2)+3(4-2x)=2x+1 equation:

Simplifying
6(x + -2) + 3(4 + -2x) = 2x + 1
Reorder the terms:
6(-2 + x) + 3(4 + -2x) = 2x + 1
(-2 * 6 + x * 6) + 3(4 + -2x) = 2x + 1
(-12 + 6x) + 3(4 + -2x) = 2x + 1
-12 + 6x + (4 * 3 + -2x * 3) = 2x + 1
-12 + 6x + (12 + -6x) = 2x + 1
Reorder the terms:
-12 + 12 + 6x + -6x = 2x + 1
Combine like terms: -12 + 12 = 0
0 + 6x + -6x = 2x + 1
6x + -6x = 2x + 1
Combine like terms: 6x + -6x = 0
0 = 2x + 1
Reorder the terms:
0 = 1 + 2x
Solving
0 = 1 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
0 + -2x = 1 + 2x + -2x
Remove the zero:
-2x = 1 + 2x + -2x
Combine like terms: 2x + -2x = 0
-2x = 1 + 0
-2x = 1
Divide each side by '-2'.
x = -0.5
Simplifying
x = -0.5`